2022
DOI: 10.1186/s13046-022-02400-7
|View full text |Cite
|
Sign up to set email alerts
|

The PRMT5-LSD1 axis confers Slug dual transcriptional activities and promotes breast cancer progression

Abstract: Background Downregulation of epithelial markers and upregulation of mesenchymal markers are the characteristics of the epithelial to mesenchymal transition (EMT) program, which provides the metastatic advantage of breast cancer. However, the mechanism underlying the switch of EMT markers remains poorly understood. Methods In this study, we used the affinity purification and mass spectrometry coupled approach to identify the interactome of Slug. CoI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Epithelial to mesenchymal transition (EMT) plays an essential role in metastasis [42]. It has been reported that PRMT5 is involved in Slug-induced EMT in breast cancer [43]. In oral squamous cell carcinoma, PRMT5 enhances metastasis by activating the EMT process [44].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial to mesenchymal transition (EMT) plays an essential role in metastasis [42]. It has been reported that PRMT5 is involved in Slug-induced EMT in breast cancer [43]. In oral squamous cell carcinoma, PRMT5 enhances metastasis by activating the EMT process [44].…”
Section: Discussionmentioning
confidence: 99%
“…PRMT5 regulates arginine symmetrical dimethylation on histone, a critical epigenetic regulator; thus a change in PRMT5 expression has a broad effect on downstream gene expression, in collaboration with another transcriptional regulator [40,41]. Unlike trimethylation on lysine, which usually presents the start of transcription process, the effect of dimethylation is more flexible, including both activation and suppression functions on different histones [42]. Therefore, the aberrant expression of PRMT5 leads to different results for different types of cells and the employment of PRMT5 inhibitors may have a selective effect [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction was conducted by using FastPure Cell/Tissue Total RNA Isolation Kit V2 (Vazyme, China) according to the manufacturer's instructions, and residual DNA in the sample is removed by following the instructions and total RNA is obtained. [ 24 ] Reverse transcription was conducted to obtain cDNA, and qPCR was performed with ChamQ Universal SYBR qPCR Master Mix (Vazyme, China). Primers are designed online using primer3.0 (https://primer3.ut.ee/).…”
Section: Methodsmentioning
confidence: 99%